2020
DOI: 10.1111/jvim.15895
|View full text |Cite
|
Sign up to set email alerts
|

Protease inhibitors, inflammatory markers, and their association with outcome in dogs with naturally occurring acute pancreatitis

Abstract: Background: Acute pancreatitis (AP) presumably is associated with pancreatic protease activation, protease inhibitor (PI) depletion, and inflammatory mediator secretion. Objectives: Examine PIs and inflammatory mediator concentrations in dogs with AP and their association with death. Animals: Thirty-one dogs diagnosed with AP based on clinical signs, ultrasonographic findings, and increased canine pancreatic lipase immunoreactivity (cPLI) and 51 healthy control dogs. Methods: Antithrombin and α 2-antiplasmin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 74 publications
(186 reference statements)
6
25
4
Order By: Relevance
“…19 Serum concentrations of acute phase reactants, such as C‐reactive protein and inflammatory cytokines, such as interleukin‐6 (IL‐6) also may be increased. 28 , 29 , 30 , 31 …”
Section: Routine Clinicopathological Featuresmentioning
confidence: 99%
“…19 Serum concentrations of acute phase reactants, such as C‐reactive protein and inflammatory cytokines, such as interleukin‐6 (IL‐6) also may be increased. 28 , 29 , 30 , 31 …”
Section: Routine Clinicopathological Featuresmentioning
confidence: 99%
“…Therefore, pancreatitis is mostly a clinical diagnosis based on 3 cornerstones, namely clinical signs, laboratory abnormalities, and ultrasonography (US). Determination of serum lipase, either as a concentration (pancreatic lipase immunoreactivity [PLI]) or an activity (1,2‐o‐dilauryl‐rac‐glycero‐3‐glutaric acid‐(6′‐methylresorufin) ester [DGGR]‐based lipase assays), has largely replaced histopathology as a surrogate gold standard for the diagnosis of pancreatitis in dogs 5‐11 . Both tests have been shown to correlate strongly 7,8,10,12‐15 .…”
Section: Introductionmentioning
confidence: 99%
“…CRP can recognize damaged cells as well as their products, and it can repair the nidus via activating complement. CRP is one of the most rapid reacting APPs, it is induced primarily by IL-1, and the plasma's CRP concentration increases within 4 h after stimulation [16,17]. Lee WC et al reported that CRP can evaluate the general health status of a herd [18].…”
Section: Discussionmentioning
confidence: 99%